Suportes para estudantes com deficiência visual no ensino superior - Silva, Daniele Sentevil da (Universidade Federal de São Carlos, 2018)
Visual impairment is a sensory alteration that affects the capture of information from the environment, which can cause, from mild to severe damage in the development and learning of who owns it. In higher education there are specific and increasingly complex demands for undergraduates, and it is extremely important to identify the support and accessibility services to guarantee the access and permanence of students with visual impairment at this stage of schooling. Thus, the present study had as general objective to analyze the support services offered by the accessibility centers of the IFES to students with visual impairment in college and, as specific objectives, to describe the performance characteristics of the accessibility centers of IFES for the student with disabilities visual; and, verify if there is an online description of services offered to students with visual impairment in the websites of the Brazilian IFES accessibility centers and, if so, what kind of information is offered. Participated in the research 10 coordinators of accessibility centers of federal college institutions in different regions of the country. They responded to an online questionnaire via google drive containing questions that addressed the subject of the survey. Also analyzed were the information on the websites of each IFES about the online description of the services offered. The data were analyzed by grouping them into three sets of information: description of the IFES, the nucleus and the coordinator; description of the services in the coordinator's view and online description of the services. The data showed that of the 10 IFES analyzed in the present study, it can be said that in terms of providing more information to describe the support services and accessibility resources of the nuclei, the IFES coordinators 1 and 3 allowed us to have a vision than the core of the institution offer to students with disabilities (visual impairment), for presenting more complete answers to the questionnaire questions. The coordinators of the IFES 2, 4, 5, 8 and 10 presented less complete data but gave a picture of how these services work and the coordinators of the IFES 6 and 9 responded very succinctly to the questionnaire of these services, which greatly hampered access to the coordinator's vision or knowledge about the services offered by the nucleus. Future research could verify or create effective online approach options for research participants, in the case of the present research, either with core coordinators, visually impaired students, or other core members who are involved in providing these services to the students.
Supports for visually impaired students in college
Keywords: Educação especial; Ensino superior; Deficiência visual; Acessibilidade; Serviços de apoio; Special education; College; Visual impairment; Accessibility; Support services; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO